Endoscopic Ischial Tuberosity Osteophyte Resection for Treatment of Ischiofemoral Impingement: A Case Report. Issue 6 (10th November 2022) - Ge, Xingtao; Cheng, Kai; Cao, Fangfang; Wang, Bin; Wang, Xishan; Wang, Chen; Li, Changhui; Chen, Longgang
Abstract: Ischiofemoral impingement is a distinct pathologic finding with abnormal osseous contact between the ischium and the lesser trochanter of the femur. Lesser trochanter excision has been recommended for recalcitrant ischiofemoral impingement through an open or endoscopic approach; however, no study has included ischial tuberosity osteophyte resection and refixation of the hamstring tendon. We report an endoscopic procedure involving ischial tuberosity osteophyte resection with refixation of the partially detached hamstring insertion through a posterior approach in the prone position. Using this technique, it is easier to reach the lesion and less likely to injure the sciatic nerve. The postoperative pain score (visual analogy score) was significantly decreased, the modified Harris hip score increased from 39 preoperatively to 86 postoperatively, and there was no adverse effect on the hamstring tendon.